PENINGKATAN KAPASITAS KADER MELALUI PENDEKATAN ACTIVE PATIENT DAN SOCIAL SUPPORT UNTUK ELIMINASI KUSTA DI TALANGO, SUMENEP, MADURA - Abdul Rahem; Anila Impian Sukorini; Yuni Priyandani; Arie Sulistyarini; Andi Hermansyah; Aniek Setiya Budiatin; Toetik Aryani; Sumarno; I Nyoman Wijaya; Gesnita Nugraheni; Ana Yuda; Umi Athiyah; Gusti Noorrizka Veronika Achmad; Mahardian Rahmadi; Farida Ifadotunnikmah (Jurnal Bakti untuk Negeri, 2026)
Talango District in Sumenep Regency faces a significant public health challenge, recording the highest leprosy prevalence in the region with 17 active cases in 2024. This issue is deeply rooted in patient non-adherence to long-term medication and the limited clinical capacity of newly appointed village health volunteers. To address this gap, this community service initiative empowered local volunteers through an intensive training program centered on the "Active Patient Method" and "Social Support" framework. The intervention utilized interactive educational sessions and clinical discussions led by a multidisciplinary team of dermatologists, public health experts, and clinical pharmacists. We evaluated the program’s impact by measuring changes in participant knowledge using a validated pre-test and post-test instrument. Statistical analysis via the Wilcoxon signed-ranks test yielded a p-value of 0.000, demonstrating a substantial and significant increase in the volunteers' understanding of leprosy management. Furthermore, the program received high appreciation from the community, with 79% of participants commending the material quality and the experts' delivery. These findings suggest that fostering social support through volunteer empowerment effectively bridges the gap in leprosy care and medication management. This initiative provides a sustainable model for community-based health interventions in remote island areas, ultimately aiming to break the chain of leprosy transmission through compassionate and informed local leadership.